PENYELENGGARAAN EfSD DALAM JALUR PENDIDIKAN DI INDONESIA - Shantini, Yanti (PEDAGOGIA, 2015)
Education for Sustainable Development has long been known in Indonesia known by the name of Education for Sustainable Development . During this time partially understood its implementation so as not to build synergy in promoting physical development towards social welfare . In this article described how the implementation of education for sustainable development in terms of three lines of education in Indonesia . Each track has a unique contribution and a different role for the progress of the nation .Keyword : ESD , access to education, social welfare.